Improvement of Work Environment Governance Based on 6S (Sort, Set in Order, Shine, Standardization, Sustain, and Safety) Method - Anasrul, Rahmad Fajri (Faculty of Economics and Business, Universitas Klabat, 2025)
PT. XYZ is a company engaged in providing telecommunications services, where one of the tasks of its employees is maintenance. In the office area where they work, there are unidentified problems that make the employees uncomfortable. This research aims to determine the 6S assessment form score and the causes of the lowest score in certain variables, as well as to provide recommendations to improve the work area. This study uses the 6S method (sort, set in order, shine, standardization, sustain, and safety) for improving the work area. The results of this study show that the 6S score for the work area is 2.437, which is classified as below the minimum acceptable level, indicating the need for improvement. A fishbone diagram is used to investigate the cause and effect, and the 6S Identification Form is used to identify areas or facilities that can be proposed for improvement. The recommendations given to improve the work area include creating clear and firm SOPs (Standard Operating Procedures), adding various shelves, replacing the existing trash bins with waste containers, and providing 6S training facilities to help employees better understand and raise awareness of the importance of implementing 6S as a work culture. These findings have practical implications for improving employee well-being and operational efficiency through systematic workplace organization, particularly for maintenance teams in the telecommunications sector.